Peran Masyarakat dalam Pemulihan Psikologis Korban Inses Berdasarkan Undang-Undang No. 12 Tahun 2022 tentang Tindak Pidana Kekerasan Seksual (Studi Kasus: Kecamatan Mendo Barat, Kabupaten Bangka) - Desi Putri Wulandari; Ela Gustiani; Melisa Natalia; Yokotani (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines the role of the community in the psychological recovery of victims of sexual violence in incest cases in Mendo Barat District based on Law No. 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS), using an empirical juridical approach through interviews, observation, and documentation. The results show that the community’s role remains limited to providing moral and material support, without addressing psychological aspects due to social stigma, the culture of silence, and limited legal understanding. Strategies for empowerment and cross-institutional collaboration are needed to realize an effective community-based recovery.